OpenStudy (anonymous):

5 years ago
OpenStudy (anonymous):

5 years ago
OpenStudy (anonymous):

5 years ago
OpenStudy (jim_thompson5910):

$\Large \sqrt{6}\left(7\sqrt{3}+6\right)$ Start off by distributing to get $\Large \sqrt{6}*7\sqrt{3}+\sqrt{6}*6$ $\Large 7\sqrt{6}*\sqrt{3}+6\sqrt{6}$ What's next?

5 years ago
OpenStudy (anonymous):

combining like terms ?

5 years ago
OpenStudy (jim_thompson5910):

close, but what do you get when you simplify $\Large \sqrt{6}*\sqrt{3}$ ??

5 years ago
OpenStudy (anonymous):

√2

5 years ago
OpenStudy (jim_thompson5910):

$\Large \sqrt{6}*\sqrt{3}$ $\Large \sqrt{6*3}$ $\Large \sqrt{18}$ so far so good?

5 years ago
OpenStudy (anonymous):

So it's (sqrt) 18 instead of (sqrt) 2 ?

5 years ago
OpenStudy (jim_thompson5910):

close, but we're not done yet

5 years ago
OpenStudy (jim_thompson5910):

$\Large \sqrt{18}$ $\Large \sqrt{9*2}$ $\Large \sqrt{9}*\sqrt{2}$ $\Large 3\sqrt{2}$ ------------------------------ So $\Large \sqrt{6}*\sqrt{3} = 3\sqrt{2}$

5 years ago
OpenStudy (jim_thompson5910):

$\Large \sqrt{6}\left(7\sqrt{3}+6\right)$ $\Large \sqrt{6}*7\sqrt{3}+\sqrt{6}*6$ $\Large 7\sqrt{6}*\sqrt{3}+6\sqrt{6}$ $\Large 7*3\sqrt{2}+6\sqrt{6}$ $\Large 21\sqrt{2}+6\sqrt{6}$ =================================== So in the end, $\Large \sqrt{6}\left(7\sqrt{3}+6\right) = 21\sqrt{2}+6\sqrt{6}$

5 years ago
OpenStudy (anonymous):

I see.

5 years ago